Alloy material of polycarbonate-polyethylene terephthalate
By mixing PET with PC and adding transesterification inhibitors and compatible agents, PC-PET alloy materials are formed, which solves the problems of high carbon emissions and unstable recycling of PC materials, and achieves low carbon emissions, high performance and environmentally friendly material characteristics.
Patent Information
- Application Number
- JP2024007748
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-15
- Filing Date
- 2024-01-23
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-01-23
AI Technical Summary
The high carbon emissions and unstable recycling sources of existing polycarbonate (PC) materials have led to their environmentally friendly challenges.
By mixing low-carbon emission polyvinylates (PET) with polycarbonate (PC), a PC-PET alloy material is formed, and a transesterification inhibitor and compatibilizer are added to the alloy to improve the compatibility and thermal stability of the material.
While reducing carbon emissions for material production, it maintains high impact strength and thermal stability, and further reduces the environmental footprint of the material by improving the recovery rate of PET.
Smart Images

Figure 2025043237000001 
Figure 2025043237000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a polycarbonate-polyethylene terephthalate alloy material. [Background technology]
[0002] Polycarbonate (PC) is widely used in fields such as home appliances and automobiles due to its excellent mechanical properties and good processing characteristics. However, PC is a material with high carbon emissions, with its carbon emissions being approximately 9kgCO2 / kg to 9.5kgCO2 / kg. Summary of the Invention [Problem to be solved by the invention]
[0003] The carbon emissions of virgin polyethylene terephthalate (PET) are only 2.6kgCO2 / kg to 3.0kgCO2 / kg. Therefore, PET is an environmentally friendly plastic material. In addition, PET has a relatively high recycling rate among plastic materials, and its recycling source is stable, and different types of recycled PET can be easily distinguished by the recycling source. In this way, PET of different colors (e.g., transparent, white, or other colors) can be recycled and made suitable for various processed products. Products made from recycled PET (r-PET) can further reduce the carbon footprint of product manufacturing. [Means for solving the problem]
[0004] The present invention provides a polycarbonate (PC)-polyethylene terephthalate (PET) alloy material that has the advantages of high impact strength and heat resistance, and can reduce the carbon emissions required for the production of the material by adding PET.
[0005] The polycarbonate-polyethylene terephthalate alloy material of the present invention includes the components of polycarbonate, polyethylene terephthalate, an ester exchange inhibitor, and a compatibilizer. The ester exchange inhibitor includes at least one of a phosphite-based ester exchange inhibitor and a phosphate-based ester exchange inhibitor. The compatibilizer includes at least one of a maleic anhydride graft copolymer, an ethylene-methyl acrylate-glycidyl methacrylate copolymer, a polyolefin elastomer graft glycidyl methacrylate, a polyethylene graft glycidyl methacrylate, and an acrylonitrile-butadiene-styrene graft glycidyl methacrylate. With respect to the total weight of the alloy material, the weight percentage of the ester exchange inhibitor is 0.5wt%-2wt%, and the weight percentage of the compatibilizer is 6wt%-15wt%. Effect of the Invention
[0006] As mentioned above, the addition of the transesterification inhibitor can inhibit the transesterification reaction between PET and PC, thereby reducing the by-products (water or alcohol) generated by the transesterification reaction that cause cracking of the PC-PET alloy material. At the same time, the addition of the compatibilizer can improve the compatibility between PC and PET, and avoid the reduction in impact strength caused by large-scale phase separation. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] Hereinafter, embodiments of the present invention will be described in detail. However, these embodiments are merely illustrative and do not limit the disclosure of the present invention.
[0008] Here, the ranges stated as "one value to another value" are a summary method to avoid listing every single value within the range in the specification. Thus, the recitation of a particular numerical range covers every value within that numerical range and any smaller numerical ranges defined by any value within that numerical range, and is the same as if every value and such smaller numerical range had been explicitly stated in the specification.
[0009] Polycarbonate (PC) is a commonly used high-performance engineering plastic with many advantages, such as high strength, wear resistance, high transparency, heat resistance, chemical resistance, and weather resistance. Therefore, PC is widely used in fields such as electronics, automobiles, construction, and medical equipment. Although PC has many advantages, the carbon emissions required to make PC and the unstable recycling sources of PC make products made using PC gradually fail to meet the needs of environmental protection. To alleviate this problem, the present invention kneads / mixes polyethylene terephthalate (PET), which has a relatively low carbon emission, with PC, so that the resulting PC-PET alloy material not only retains the advantages of high impact strength and heat resistance, but also has the advantage of being environmentally friendly.
[0010] In order for the PC-PET alloy material to have sufficiently excellent properties, in the process of producing the PC-PET alloy material, in addition to adding PC and PET, other additives such as ester exchange inhibitors, compatibilizers, strengthening agents, lubricants, crystallization inhibitors, antioxidants, etc. may also be added to the PC-PET alloy material in some embodiments. The components in the PC-PET alloy material are described below.
[0011] Polycarbonate (PC) PC may include virgin PC, recycled PC, or a combination thereof. Virgin PC is generally existing new PC. Recycled PC may be physically regenerated PC. In some embodiments, the weight percentage of PC is 30wt%-50wt% based on the total weight of the final synthesized PC-PET alloy material.
[0012] Polyethylene terephthalate (PET) PET may include virgin PET, recycled PET, or a combination thereof. Virgin PET is generally pre-existing new PET. Recycled PET may include physically regenerated PET and / or chemically regenerated PET.
[0013] For example, the method of obtaining recycled PET includes collecting various kinds of waste polyester resin materials. The waste polyester resin materials are classified according to type, color, and use. Further, the waste polyester resin materials are compressed and baled, and then transported to a waste disposal site.
[0014] In some embodiments, the waste polyester resin material is recycled PET bottles, film materials, fibers, etc., but the present invention is not limited thereto. Other parts on the waste polyester resin material (e.g., PET bottle caps, labels, adhesives) are removed. Then, the waste polyester resin material is cut and crushed to obtain a processed recycled polyester material (i.e., recycled polyethylene terephthalate (r-PET)) to facilitate the subsequent manufacturing process.
[0015] In a continuous process, the shredded r-PET pieces are then melted at high temperature in an extruder to form a r-PET molten material, which may include a single-screw extruder, a twin-screw extruder, a planetary extruder, etc.
[0016] Then, in a continuous process, the r-PET melt material is placed into a pressure-controlled liquid thickening extrusion system where the material can be heated to a temperature of 230°C to 300°C for 15 to 60 minutes under low air pressure of 1 millibar (mbar) to 6 mbar, which has the effect of increasing the intrinsic viscosity of the r-PET melt material and forming the recycled polyester resin. The recycled polyester resin (i.e., r-PET) has an intrinsic viscosity (IV) of 0.6 dL / g to 0.86 dL / g.
[0017] In some embodiments, the intrinsic viscosity of r-PET is controlled to optimize the subsequent manufacturing process of the PC-PET alloy material.
[0018] In a continuous process, the material properties of r-PET may be modified by a modification extruder.
[0019] First, the modifiers such as the transesterification inhibitor and the compatibilizer are mixed uniformly based on the ratio, and then the modifiers are fed into the modified extruder based on the ratio using a loss-in-weight feeder, and mixed with the recycled polyester resin in the molten state to form physically recycled modified polyester particles with different functions. The types of the modified extruder include single screw extruder, twin screw extruder, planetary extruder, etc. In some embodiments, in addition to the modification by the transesterification inhibitor and the compatibilizer, the toughening agent, lubricant, crystallization inhibitor, antioxidant, etc. are also added to the modified extruder to modify the r-PET.
[0020] In some embodiments, the weight percentage of PET is 50wt%-70wt% based on the total weight of the final synthesized PC-PET alloy material. Generally, PET has low carbon emission and stable recycling source. Therefore, in order to be more environmentally friendly, it is better to make the content of PET in the PC-PET alloy material higher than the content of PC.
[0021] Esterification inhibitor When PC and PET are compounded / mixed, transesterification may occur between them. The by-products (water or alcohol) produced by the transesterification will crack the polyester, causing problems such as molecular weight reduction, deterioration, material embrittlement (reduced impact resistance), and cause both PC and PET to lose good mechanical properties.
[0022] In order to avoid excessive transesterification, it is necessary to add an appropriate amount of transesterification inhibitor when kneading / mixing PC and PET. The transesterification inhibitor includes, for example, at least one of a phosphite-based transesterification inhibitor and a phosphate-based transesterification inhibitor. The phosphite-based transesterification inhibitor is, for example, triphenyl phosphite, bis(2,4-dicumylphenyl)pentaerythritol diphosphite, tris(2,4-di-tert-butylphenyl)phosphite, and the phosphate-based transesterification inhibitor is, for example, sodium dihydrogen phosphate, disodium hydrogen phosphate, disodium dihydrogen pyrophosphate, and triphenyl phosphate.
[0023] Adding too much or too little transesterification inhibitor will have a negative effect on the PC-PET alloy material produced thereafter. The weight percentage of the transesterification inhibitor is 0.5wt%-2wt%, preferably 0.5wt%-1wt%, based on the total weight of the PC-PET alloy material. When the weight percentage of the transesterification inhibitor is less than 0.5wt%, excessive transesterification reaction occurs between PC and PET, which reduces the heat resistance and processability of the PC-PET alloy material. When the weight percentage of the transesterification inhibitor exceeds 2wt%, the compatibility between PET and PC is low, which causes the problem of reduced impact strength. In addition, excessive transesterification inhibitor increases the cost.
[0024] Compatibilizer Compatibilizers can be used to improve the compatibility between PC and PET, thereby controlling the dispersion size of PC and PET. For example, when one of PC and PET is the parent phase and the other is the dispersed phase, the compatibilizer helps to disperse the dispersed phase more uniformly in the parent phase, thereby preventing the separation of the two phases.
[0025] The combination of the transesterification inhibitor and the compatibilizer can improve the compatibility between PC and PET and at the same time avoid the by-products generated by the transesterification reaction. A suitable amount of the compatibilizer is desirable. The compatibilizer may be, for example, a maleic anhydride graft copolymer (e.g., maleic anhydride graft polyethylene (PE-MA), maleic anhydride graft polypropylene (PP-MA), maleic anhydride graft acrylonitrile-butadiene-styrene (ABS-MA), ethylene-methyl acrylate copolymer (E-MAC), ethylene-methyl acrylate-glycidyl methacrylate copolymer (E-MA-GMA), polyolefin elastomer graft glycidyl methacrylate (POE-g-GMA), polyethylene graft glycidyl methacrylate, The polymers may include at least one of the following: PE-g-GMA, acrylonitrile-butadiene-styrene graft glycidyl methacrylate (ABS-g-GMA).
[0026] Adding too much or too little compatibilizer will have a negative effect on the PC-PET alloy material produced subsequently. The weight percentage of the compatibilizer is 6wt%-15wt%, with 8wt%-12wt% being preferred, relative to the total weight of the PC-PET alloy material. When the weight percentage of the compatibilizer is less than 6wt%, the compatibility between PC and PET is low, and PC and PET easily phase separate. When the weight percentage of the compatibilizer is more than 15wt%, the impact strength and toughness of the material can be greatly improved, but the tensile strength, bending strength and heat resistance temperature will be greatly reduced, since the compatibilizer is an elastomeric material.
[0027] Reinforcement The toughening agent can be used to improve the impact strength of the PC-PET alloy material. For example, the toughening agent can be used to improve the impact strength of the parent phase in the PC-PET alloy material. In some embodiments, in the PC-PET alloy material, the parent phase is PET and the dispersed phase includes PC.
[0028] In some embodiments, the toughening agent comprises at least one of polyolefin elastomer (POE), acrylics (ACR), methyl acrylate-butadiene-styrene copolymer (MBS), ethylene-butyl acrylate-glycidyl methacrylate copolymer (PTW), or other suitable materials.
[0029] In some embodiments, the weight percentage of the reinforcement agent is between 1 wt% and 5 wt%, with 2 wt% to 3 wt% being preferred, based on the total weight of the PC-PET alloy material.
[0030] Lubricants Lubricants can improve the fluidity of materials. Adding lubricants to PC-PET alloy materials can facilitate the application of PC-PET alloy materials during the injection molding process and the release process of mold molding.
[0031] In some embodiments, the lubricant comprises at least one of a stearate, a polyethylene wax, a modified siloxane, a fluoroplastic, or other suitable material.
[0032] In some embodiments, the weight percentage of the lubricant is between 0.1 wt% and 2 wt%, with 0.5 wt% to 1 wt% being preferred, based on the total weight of the PC-PET alloy material.
[0033] Crystallization Inhibitor Crystallization inhibitors are used to reduce the crystallization rate of PET. Generally, PC is an amorphous plastic, so if PET is too crystalline, the two phases will separate when PC and PET are kneaded / mixed due to the incompatibility between the crystalline and amorphous phases. By reducing the crystallization rate of PET with a crystallization inhibitor, it is possible to obtain PET with low crystallinity or even amorphous PET, thus avoiding the phase separation problem.
[0034] In some embodiments, the crystallization inhibitor comprises at least one of polyester modified by isophthalic acid (IPA) copolymerization (e.g., PET modified by 20% IPA copolymerization, i.e., IPET), polyester modified by cyclohexanedimethanol (CHDM) copolymerization, and other suitable materials. Polyester modified by CHDM copolymerization is, for example, polyethylene terephthalate glycol-modified (PETG) or polyethylene cyclohexanedimethanol terephthalate (PCTG) modified by CHDM copolymerization.
[0035] In some embodiments, the weight percentage of the crystallization inhibitor is greater than or equal to 0 wt % and less than or equal to 5 wt %, based on the total weight of the PC-PET alloy material.
[0036] Antioxidants In some embodiments, the antioxidant comprises at least one of a phenolic antioxidant, a blend antioxidant, and a phosphite antioxidant.
[0037] In some embodiments, the weight percentage of the antioxidant is between 0.5 wt% and 2 wt%, based on the total weight of the PC-PET alloy material.
[0038] The present invention also proposes a product made from the PC-PET alloy material as engineering plastic particles by processing methods, which can include extrusion, injection molding, molding, or plate processing.
[0039] The PC-PET alloy material of the present invention will be described in detail with reference to the following experimental examples, but the present invention is not limited to these experimental examples.
[0040] Experimental Example The r-PET polyester particles were modified using an ester exchange inhibitor, a compatibilizer, a toughening agent, a lubricant, a crystallization inhibitor, and an antioxidant to obtain the first modified r-PET polyester particles. The first modified r-PET polyester particles contained 86.5 wt% r-PET (IV is 0.8), 8 wt% compatibilizer (E-MA-GMA), 2 wt% toughening agent (POE), 1 wt% crystallization inhibitor (PET modified by 20% isophthalic acid copolymerization), 0.5 wt% lubricant (polyethylene wax), 1 wt% ester exchange inhibitor (phosphite, e.g., tris(2,4-di-tert-butylphenyl) phosphite), and 1 wt% antioxidant (blend antioxidant). The first modified r-PET polyester particles and PC were then mixed in different ratios to obtain the PC-PET alloy materials of Example 1 and Example 2 in Table 1. In addition, acrylonitrile-butadiene-styrene (ABS) (AG12A0) from Formosa Chemicals & Fibre Corporation of Taiwan was provided as Comparative Example 1, and alloy materials of PC-PET obtained by mixing the first modified r-PET polyester particles with PC without using any transesterification inhibitor, compatibilizer, reinforcing agent, lubricant, crystallization inhibitor, or antioxidant were provided as Comparative Example 2 and Comparative Example 3. Various property tests were performed on Comparative Example 1 to Comparative Example 3, and the obtained results are shown in Table 1. The ASTM standard test pieces produced in each of the Examples and Comparative Examples were evaluated according to the following methods. Specific Gravity: The density of a material relative to the density of pure water at 4°C. Tested according to ASTM D792 standard. Impact strength: Tested according to ASTM D256 standard. The value obtained indicates the total energy that the test specimen can withstand when it breaks. The higher the value, the greater the impact strength (or the strength of the test specimen) that the test specimen can withstand. The unit is kg-cm / cm. Tensile strength: The test was performed according to the ASTM D638 standard. The obtained value indicates the total energy that the test specimen can withstand against tensile deformation. The higher the value, the greater the tensile strength that the test specimen can withstand. The unit is MPa. Flexural strength: Measured according to the ASTM D790 standard test method to obtain a value that represents the resistance of the test piece to bending strain and deformation. The higher the value, the higher the flexural strength of the test piece. Flexural modulus: Tested according to ASTM D790 standard. The value obtained indicates the total energy that the test specimen can withstand in bending deformation. The higher the value, the higher the stiffness of the test specimen. The unit is MPa. Heat Distortion Temperature (HDT): According to the ASTM D648 standard, a load of 1.82 MPa was applied to the test specimen. HDT is a parameter that indicates the relationship between heat and strain of the test specimen, and is an index for measuring the heat resistance of a polymer. During the test, a constant load is applied to the polymer, and the temperature is increased at a constant rate until the temperature corresponding to the specified strain is reached. Shrinkage: Measured according to the ASTM D955 standard test method, "shrinkage" refers to the difference (percentage) between the dimensions of a plastic product that has cooled and solidified from a mold and the dimensions of the original mold.
[0041] [Table 1]
[0042] As can be seen from Table 1, the PC-PET alloy material obtained by mixing the modified r-PET polyester particles with PC has higher impact strength and higher heat distortion temperature (HDT), that is, the PC-PET alloy materials of Examples 1 and 2 have better mechanical strength and thermal stability.
[0043] Table 2 provides the alloy materials of PC-PET obtained by mixing the PC and the second modified r-PET polyester particles or the third modified r-PET polyester particles according to some embodiments of the present invention. The second modified r-PET polyester particles include modified r-PET polyester particles containing 86.5 wt% r-PET (IV is 0.8), 8 wt% compatibilizer (ethylene-methyl acrylate copolymer, E-MA), 2 wt% toughening agent (POE), 1 wt% crystallization inhibitor (PET modified with 20% isophthalic acid copolymerization), 0.5 wt% lubricant (polyethylene wax), 1 wt% transesterification inhibitor (phosphite, e.g., tris(2,4-di-tert-butylphenyl) phosphite, and 1 wt% antioxidant (blend antioxidant).
[0044] The third modified r-PET polyester particles comprised modified r-PET polyester particles containing 86.5 wt% r-PET (IV of 0.8), 8 wt% compatibilizer (POE-g-GMA), 2 wt% toughening agent (POE), 1 wt% crystallization inhibitor (PET modified with 20% isophthalic acid copolymerization), 0.5 wt% lubricant (polyethylene wax), 1 wt% transesterification inhibitor (phosphite, tris(2,4-di-tert-butylphenyl) phosphite, and 1 wt% antioxidant (blend antioxidant).
[0045] [Table 2]
[0046] As can be seen from Table 2, the PC-PET alloy materials of Examples 5 and 6 have higher impact strength and flexural strength than the PC-PET alloy materials of Examples 3 and 4. It can be seen that the third modified r-PET polyester particles can more effectively improve the impact strength and flexural strength of the PC-PET alloy materials. [Industrial Applicability]
[0047] The polycarbonate-polyethylene terephthalate alloy material of the present invention is suitable for various processed products.
Claims
1. Polycarbonate and Polyethylene terephthalate, an ester exchange inhibitor comprising at least one of a phosphite-based ester exchange inhibitor and a phosphate-based ester exchange inhibitor; a compatibilizer comprising at least one of maleic anhydride graft copolymer, ethylene-methyl acrylate-glycidyl methacrylate copolymer, polyolefin elastomer graft glycidyl methacrylate, polyethylene graft glycidyl methacrylate, and acrylonitrile-butadiene-styrene graft glycidyl methacrylate; and wherein, based on a total weight of the alloy material, a weight percentage of the transesterification inhibitor is between 0.5 wt % and 2 wt %, and a weight percentage of the compatibilizer is between 6 wt % and 15 wt %.
2. 2. The polycarbonate-polyethylene terephthalate alloy material of claim 1, further comprising a toughening agent, the toughening agent comprising at least one of a polyolefin elastomer, an acrylate, a methyl acrylate-butadiene-styrene copolymer, and an ethylene-butyl acrylate-glycidyl methacrylate copolymer.
3. 3. The polycarbonate-polyethylene terephthalate alloy material of claim 2, wherein the weight percentage of said reinforcement agent is between 1 wt% and 5 wt% based on the total weight of said alloy material.
4. 2. The polycarbonate-polyethylene terephthalate alloy material of claim 1, further comprising a crystallization inhibitor, the crystallization inhibitor comprising at least one of a polyester modified by isophthalic acid copolymerization and a polyester modified by cyclohexane dimethanol copolymerization.
5. 5. The polycarbonate-polyethylene terephthalate alloy material of claim 4, wherein the weight percentage of said crystallization inhibitor is greater than 0 wt % and less than or equal to 5 wt %, based on the total weight of said alloy material.
6. 2. The polycarbonate-polyethylene terephthalate alloy material of claim 1, further comprising a lubricant, the lubricant comprising at least one of a stearate, a polyethylene wax, a modified siloxane, and a fluororesin.
7. 7. The polycarbonate-polyethylene terephthalate alloy material of claim 6, wherein the weight percentage of said lubricant is between 0.1 wt% and 2 wt% based on the total weight of said alloy material.
8. 2. The polycarbonate-polyethylene terephthalate alloy material of claim 1, further comprising an antioxidant, the antioxidant comprising at least one of a phenol-based antioxidant, a blend-based antioxidant, and a phosphite-based antioxidant.
9. 9. The polycarbonate-polyethylene terephthalate alloy material of claim 8, wherein the weight percentage of said antioxidant is between 0.5 wt% and 2 wt%, based on the total weight of said alloy material.
10. 2. The polycarbonate-polyethylene terephthalate alloy material according to claim 1, wherein the intrinsic viscosity of the polyethylene terephthalate is 0.6 dL / g to 0.86 dL / g, and the content of the polyethylene terephthalate in the polycarbonate-polyethylene terephthalate alloy material is greater than the content of the polycarbonate.
Citation Information
Patent Citations
Scratch-Resistant-Flame-Retardant Thermoplastic Resin Composition
JP2009533520A